Supraparticles Composed of Graphitic Carbon Nitride Nanoparticles and Silica-Supported Horseradish Peroxidase as Customizable Hybrid Catalysts for Photo-Biocatalytic Cascade Reactions in Continuous Flow - Herbig, Bettina; Cermjani, Egzon; Hanselmann, Doris; Prieschl, Johannes; Schmitt, Angelika; Moritz, Michael; Papp, Christian; Nölke, Greta; Di Fiore, Stefano; Deckers, Christoph; Rehm, Thomas H.; Wintzheimer, Susanne (Advanced Functional Materials, 2025)
In green and sustainable chemistry, coupling biocatalysis and photocatalysis in cascade processes is particularly appealing. It enables reactions at ambient temperature in aqueous solutions with light as an abundant energy source. Additionally, it merges the high reactivity of photocatalysts with the unique selectivity of biocatalysts. However, such cascade processes, especially when conducted in one-pot mode, pose the challenges of mutual catalyst deactivation and opposite optimal conditions for each catalytic step. In this work, the design of hybrid supraparticles consisting of the nanoparticular photocatalyst graphitic carbon nitride and the enzyme horseradish peroxidase immobilized on silica nanoparticles is proposed. A compatibility range where both catalysts can coexist within the hybrid supraparticles and function effectively, both in one-pot batch and continuous flow processes, is identified using the photocatalytic hydrogen peroxide production and the enzymatic 3,3′,5,5′-tetramethylbenzidine conversion as a model cascade reaction.
CRIS-Team Scopus Importer:2025-12-05
Keywords: cascade reaction; flow chemistry; graphitic carbon nitride; horse radish peroxidase; hybrid catalyst; photobiocatalysis; supraparticles